CIPP Evaluation of the Child-Friendly Madrasah Program at MAN 2 Kulonprogo, Yogyakarta - Irwanto; Purwanto; Khuriyah; Aulia, Nurul (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2026)
The Child-Friendly Madrasah (MRA) Program is a government policy designed to create a safe, comfortable, inclusive, and violence-free educational environment. MAN 2 Kulonprogo, which received a provincial award for child-friendly education in the Special Region of Yogyakarta, was evaluated to determine the program’s implementation comprehensively. This study used the CIPP (Context, Input, Process, Product) evaluation model with a mixed-methods approach. The quantitative sample consisted of 233 students selected through simple random sampling from a population of 688 students, while qualitative informants were selected purposively and included the madrasah principal, vice principal, teachers, students, and committee members. Quantitative data were collected using a Likert-scale questionnaire and analyzed descriptively and comparatively. Qualitative data were obtained through observation, in-depth interviews, and documentation and analyzed using the Miles and Huberman interactive model. Data validity was strengthened through source and technique triangulation. The results showed that: (1) the program context met the MRA indicators through the establishment of an MRA Team, spaces for student participation, and a strong humanistic culture; (2) the initial input condition was in the high category, with a mean score of 138.21, and was supported by adequate institutional readiness; (3) implementation proceeded systematically through holistic and participatory preparation, planning, and execution; and (4) the product evaluation showed an increase in mutual respect from a mean of 138.21 to 140.28, with both scores remaining in the high category. The MRA program at MAN 2 Kulonprogo was implemented effectively and has the potential to be developed as a character-education model in Islamic educational institutions.